The Effects of Ginsenoside Compound K Against Epilepsy by Enhancing the γ-Aminobutyric Acid Signaling Pathway - Zeng, Xiangchang; Hu, Kai; Chen, Lulu; Zhou, Luping; Luo, Wei; Li, Chaopeng; Zong, Wenjing; Chen, Siyu; Gao, Qing; Zeng, Guirong; Jiang, Dejian; Li, Xiaohui; et al. (Frontiers in Pharmacology, 2018)
The imbalance between the GABA-mediated inhibition and the glutamate-mediated excitation is the primary pathological mechanism of epilepsy. GABAergic and glutamatergic neurotransmission have become the most important targets for controlling epilepsy. Ginsenoside compound K (GCK) is a main metabolic production of the ginsenoside Rb1, Rb2, and Rc in the intestinal microbiota. Previous studies show that GCK promoted the release of GABA from the hippocampal neurons and enhanced the activity of GABAA receptors. GCK is shown to reduce the expression of NMDAR and to attenuate the function of the NMDA receptors in the brain. The anti-seizure effects of GCK have not been reported so far. Therefore, this study aimed to investigate the effects of GCK on epilepsy and its potential mechanism. The rat model of seizure or status epilepticus (SE) was established with either Pentylenetetrazole or Lithium chloride-pilocarpine. The Racine’s scale was used to evaluate seizure activity. The levels of the amino acid neurotransmitters were detected in the pilocarpine-induced epileptic rats. The expression levels of GABAARα1, NMDAR1, KCC2, and NKCC1 protein in the hippocampus were determined via western blot or immunohistochemistry after SE. We found that GCK had deceased seizure intensity and prolonged the latency of seizures. GCK increased the contents of GABA, while the contents of glutamate remained unchanged. GCK enhanced the expression of GABAARα1 in the brain and exhibited a tendency to decrease the expression of NMDAR1 protein in the hippocampus. The expression of KCC2 protein was elevated by the treatment of GCK after SE, while the expression of NKCC1 protein was reversely down-regulated. These findings suggested that GCK exerted anti-epileptic effects by promoting the hippocampal GABA release and enhancing the GABAAR-mediated inhibitory synaptic transmission.